The PENGARUH METACOGNITION STRATEGI DALAM MEMBACA KOMPREHENSIF DALAM TEKS DESKRIPTIF DI INSTITUT KESEHATAN DELI HUSADA DELI TUA 2019 - sulastri br ginting (Jurnal Penelitian Kesmasy, 2020)
The study is focused on finding out the effect of applying Metacognition Strategy on students’ reading comprehension in reading descriptive text. This study conducted on experimental quantitative design. The population of the research was the Pharmacy students at Institut Deli Husada Deli Tua. There are three hundred forty six students at pharmacy to be the sample of the research. This study was conducted by two randomized groups named Experimental Group and Control Group. The Experimental Group was taught by using Metacognition Strategy but in Control Group didn’t be taught by using Metacogniton Strategy. The instrument of collecting the data was multiple choice tests which consisted of 25 questions. The research Obtain the reliability of the test by using Kuder-Richardson (KR-21) formula. The calculation shown the reliability was 0.57 (Moderate). The data were analyzed by using t-test formula. At the level of significance 0.05 with the deegree of freedom (df) 58, t-observed is 4.1 while t-table is 1.67. Then F-value is 1.41 and F-table is 1.84. It means that there was significant effect of applying Metacogniton strategy on students’ Reading Comprehension in reading descriptive text. So, the conclusion is the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is totally accepted.